Faktor-Faktor yang Mempengaruhi Minat Generasi Z dalam Menggunakan Dompet Digital (Studi Kasus Generasi Z di Kabupaten Nganjuk) - Setyaangraini, Salsabilla Putri; Susandini, Aprilina (Management Department of Economics and Business Of Trunojoyo Madura University, 2025)
The purpose of this study was to determine whether or not the influence of service features, perceived ease of use, perceived benefits, perceived security, and perceived risk on interest in using digital wallets in generation Z Nganjuk Regency, Kertosono District, Tembarak Village. This research was conducted using quantitative methods with data collection techniques using direct questionnaires online via google form. The population in this study is generation Z, with the sampling technique used is purposive sampling method and obtained a sample size of 125 respondents, namely generation Z aged 17 to 27 years, domiciled in Tembarak Village and knowing or using digital wallets. Primary data processing uses Statistical Package for the Social Sciences (SPSS) version 25 analysis techniques through multiple linear regression analysis methods. The results of this study indicate that the variables of service features, perceived ease of use, perceived benefits, and perceived security partially have a positive and significant effect on interest in using digital wallets in generation Z in Nganjuk Regency, Kertosono District, Tembarak Village, while the variable risk perception has a negative and insignificant effect on interest in using digital wallets in generation Z in Nganjuk Regency, Kertosono District, Tembarak Village.